PRODUKSI BIOETANOL TONGKOL JAGUNG (ZEA MAYS) DARI HASIL PROSES DELIGNIFIKASI - Fitriani, Fitriani; Bahri, Syaiful; Nurhaeni, Nurhaeni (Natural Science: Journal of Science and Technology, 2013)
The research about ?The Production of Bioetanol in Corn cob waste (Zea Mays) of Resulting The Delignation Process?. The aim of this research  is to find out the highest weight of cellulose which contained in the corn cob waste. Then Cellulose which has been obtained, it was done on delignification process by using NaOH in variety of soaking time. To achieve the goal, then the application of the treatment effect of soaking time on corn cob waste powder on weight of cellulose was done. On the effect of soaking time on the powder of corn cob waste was applied   the six levels each 12 hours, 16 hours, 20 hours, 2 hours, 28 hours and 32 hours. Based on the result, it showed that the weight of cellulose is 5,729 g at 28 hours on soaking time. The use of soaking time which was applied for delignification process NaOH on the yield of cellulose. Cellulose of hydrolysis corn cob waste powder with H2SO4 10% and the result of fermentation of hydrolysis yeast cells immobilized. The level of glukosa is 43 % and 6 % for etanol. The result of sugar fermentation is done at the room temperature for 48 hours.